Effect on mortality of different routes of administration and loading dose of aspirin in patients with ST-segment elevation acute myocardial infarction treated with primary angioplasty. Issue 4 (June 2020) - Rossi, Rosario; Bagnacani, Alessandra; Sgura, Fabio; Enrique Monopoli, Daniel; Coppi, Francesca; Talarico, Marisa; Rolando, Cristina; Boriani, Giuseppe
Abstract : Background: Aspirin is the cornerstone of the anti-platelet therapy during the acute phase of ST-segment elevation myocardial infarction (STEMI), and it can be administrated orally or intravenously. The oral loading dose of aspirin is well characterized, whereas there are little data on the optimal intravenous (IV) loading dose. Aim: To confirm if the mortality of patients treated with a loading dose of IV aspirin was comparable to that of patients treated with the most usual aspirin per os. Patients and methods: We analyzed the overall mortality during hospitalization and at 1 year follow-up among 756 consecutive patients with STEMI. Four hundred seventy-eight (63.2%) patients received per os and 278 (36.8%) IV aspirin. We divided the 278 patients of the IV aspirin group into two subgroups, based on the median value of the dose of aspirin used as a load. Results: The per os aspirin group took 234 ± 138 mg of aspirin per os at the first medical contact; the IV low-dose group 194 ± 87 mg, and the IV high-dose group 483 ± 194 mg of IV aspirin. No differences were observed in mortality rate after 1-year of follow-up. In-hospital mortality resulted significantly higher (9.3%) in the IV high-dose group respect to the IV low-dose one (5.0%) and per os aspirin group (6.0%) ( P < 0.01 for both). Conclusion: In this retrospective study, high dose IV aspirin loading in STEMI increased intra-hospital mortality. Further study is necessary to define the optimal dose of intravenous aspirin in STEMI.